Implementasi Seri Ramadhan dalam Manajemen Strategis Pelaku UMKM di Martapura - Kurratu'ayunina (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in supporting local and national economic development, particularly through employment generation and income distribution. Seasonal religious events such as Ramadan significantly influence consumption patterns and market dynamics, creating both opportunities and challenges for MSMEs. This study aims to analyze the implementation of the “Seri Ramadhan” phenomenon within the strategic management practices of MSMEs in Martapura, focusing on the periods before and after Ramadan. The research employed a qualitative descriptive approach with field study methods. Data were collected through in-depth interviews, direct observation, and documentation involving selected MSME actors in the culinary, fashion, and retail sectors. The findings indicate that prior to Ramadan, MSMEs emphasize strategic planning through product innovation, stock preparation, promotional intensification, and operational adjustments. After Ramadan, they conduct performance evaluations, inventory control, and strategic realignment to maintain business sustainability. The study highlights that Ramadan is not merely a short-term sales opportunity but also a strategic momentum integrated into broader business planning cycles. The implications suggest that adaptive and cyclical strategic management enhances MSME resilience and competitive advantage in seasonal markets.